(x+m)(x+m)=x(x-m)

Simple and best practice solution for (x+m)(x+m)=x(x-m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+m)(x+m)=x(x-m) equation:


Simplifying
(x + m)(x + m) = x(x + -1m)

Reorder the terms:
(m + x)(x + m) = x(x + -1m)

Reorder the terms:
(m + x)(m + x) = x(x + -1m)

Multiply (m + x) * (m + x)
(m(m + x) + x(m + x)) = x(x + -1m)
((m * m + x * m) + x(m + x)) = x(x + -1m)

Reorder the terms:
((mx + m2) + x(m + x)) = x(x + -1m)
((mx + m2) + x(m + x)) = x(x + -1m)
(mx + m2 + (m * x + x * x)) = x(x + -1m)
(mx + m2 + (mx + x2)) = x(x + -1m)

Reorder the terms:
(mx + mx + m2 + x2) = x(x + -1m)

Combine like terms: mx + mx = 2mx
(2mx + m2 + x2) = x(x + -1m)

Reorder the terms:
2mx + m2 + x2 = x(-1m + x)
2mx + m2 + x2 = (-1m * x + x * x)
2mx + m2 + x2 = (-1mx + x2)

Add '-1x2' to each side of the equation.
2mx + m2 + x2 + -1x2 = -1mx + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
2mx + m2 + 0 = -1mx + x2 + -1x2
2mx + m2 = -1mx + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
2mx + m2 = -1mx + 0
2mx + m2 = -1mx

Solving
2mx + m2 = -1mx

Solving for variable 'm'.

Reorder the terms:
2mx + mx + m2 = -1mx + mx

Combine like terms: 2mx + mx = 3mx
3mx + m2 = -1mx + mx

Combine like terms: -1mx + mx = 0
3mx + m2 = 0

Factor out the Greatest Common Factor (GCF), 'm'.
m(3x + m) = 0

Subproblem 1

Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0

Subproblem 2

Set the factor '(3x + m)' equal to zero and attempt to solve: Simplifying 3x + m = 0 Reorder the terms: m + 3x = 0 Solving m + 3x = 0 Move all terms containing m to the left, all other terms to the right. Add '-3x' to each side of the equation. m + 3x + -3x = 0 + -3x Combine like terms: 3x + -3x = 0 m + 0 = 0 + -3x m = 0 + -3x Remove the zero: m = -3x Simplifying m = -3x

Solution

m = {0, -3x}

See similar equations:

| 6(y-1)=3y+12 | | 5x^6*3x^5*4x^3= | | 13x+5(x-4)=8x+5 | | 3p^6q^7*7p^2q^1= | | -2(8s-5)=-16s | | -7x^2-9=0 | | -20p+4=2(-10p+2) | | -3(5-5z)=-5(3-3z) | | -3.43+5b=16.84+5b-2.08 | | 18.7h+13.33=11.7h-16.77 | | 4r-5=13r+16 | | -4=2-x-x | | 8x+5y+4z-4x+2z-7y= | | 13-a+4a=4 | | 13-1+4a=4 | | 6*985= | | 7(m+8)= | | 160=-15t^2+105t+10 | | -1=150a | | 0=3x^3-4x | | (5x+1)*3=48 | | 40x+60y=420 | | 15x-30=6x | | 7x+2=12x^2+4x-8 | | 9x^4-40x^2+16=0 | | 7x+2=12x | | (x+2)2=y | | 5+2(5x-4)=7-5(2x+1) | | (2x-1)(4x+3)=7-22x | | ln(x+12)+ln(2)=2ln(x) | | 7+2(3x-4)=5-4(2x+1) | | (6-y)+(1+4y)=43 |

Equations solver categories